2014
DOI: 10.1037/a0034913
|View full text |Cite
|
Sign up to set email alerts
|

The malleability of working memory and visuospatial skills: A randomized controlled study in older adults.

Abstract: There is accumulating evidence that training on working memory (WM) generalizes to other nontrained domains, and there are reports of transfer effects extending as far as to measures of fluid intelligence. Although there have been several demonstrations of such transfer effects in young adults and children, they have been difficult to demonstrate in older adults. In this study, we investigated the generalizing effects of an adaptive WM intervention on nontrained measures of WM and visuospatial skills. We rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 99 publications
(175 reference statements)
4
52
0
1
Order By: Relevance
“…To date, studies approaching this issue have been scarce (but see Brehmer et al, 2012;Zinke et al, 2014), although several studies have shown transfer effects after WM training to other cognitive functions, including verbal learning and memory (Richmond et al, 2011), language comprehension (Carretti et al, 2012), and VS skills (Stepankova et al, 2014). Executive functions, however, are essential in successful autonomous functioning in everyday life (Miyake & Friedman, 2012) and they are generally negatively affected by aging (Raz, 2000;Salthouse et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To date, studies approaching this issue have been scarce (but see Brehmer et al, 2012;Zinke et al, 2014), although several studies have shown transfer effects after WM training to other cognitive functions, including verbal learning and memory (Richmond et al, 2011), language comprehension (Carretti et al, 2012), and VS skills (Stepankova et al, 2014). Executive functions, however, are essential in successful autonomous functioning in everyday life (Miyake & Friedman, 2012) and they are generally negatively affected by aging (Raz, 2000;Salthouse et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Both near and far transfer were also found in a study by Carretti, Borella, Zavagnin, and De Beni (2012), who observed improvements in a verbal WM updating task as well as in language comprehension after verbal WM span training. A study by Stepankova et al (2014) showed near transfer after verbal n-back training to untrained measures of WM and far transfer to visuospatial (VS) skills.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, we have previously described a dose-dependent relationship between training and transfer, such that more training leads to more gain (Jaeggi et al, 2008). This relationship has been replicated in some studies (Basak, Boot, Voss, & Kramer, 2008;Dahlin, Backman, Neely, & Nyberg, 2009;Stepankova et al, 2014;Tomic & Klauer, 1996), but not others . We hypothesized that this dosage effect would hold up across studies in the form of a positive correlation between number of training sessions and degree of transfer.…”
Section: Introductionmentioning
confidence: 87%
“…The centrality of attention and working memory to cognitive aging has made them attractive targets for training (e.g., Stepankova et al, 2014; see reviews by Backman and Nyberg (2013); Lovden et al (2010); Lustig et al (2009)). Patterns of improvement and transfer in these interventions also provide clues as to the mechanisms that underlie age effects on cognition.…”
Section: Interventions and Trainingmentioning
confidence: 99%